Flower fields and pesticide use interactively shape pollen beetle infestation and parasitism in oilseed rape fields. Issue 1 (23rd October 2021) - Krimmer, Elena; Martin, Emily A.; Holzschuh, Andrea; Krauss, Jochen; Steffan‐Dewenter, Ingolf
Abstract: Pollen beetles ( Brassicogethes spp.) are the main pests of oilseed rape (OSR, Brassica napus ) in Europe and responsible for massive yield losses. Upcoming pesticide resistances highlight the need for other means of crop protection, such as natural pest control. Sown flower fields aim to counteract the decrease of insect biodiversity in agricultural landscapes by providing resources to ecosystem service providers. However, the optimal age and size of flower fields to increase natural pest control is still unclear. We conducted experiments on 31 OSR fields located along a gradient of landscape‐scale semi‐natural habitat (SNH). OSR fields were located adjacent to flower fields which differed in age, continuity and size, or adjacent to crop fields or calcareous grasslands. Pesticide‐free areas were established to examine interactive effects of pesticide use and flower field characteristics. The abundance of pollen beetle adults and larvae, parasitism and superparasitism rates in OSR were recorded at increasing distances to the adjacent sites. Flower fields and calcareous grasslands increased pollen beetle parasitism when compared to OSR fields neighbouring crop fields. The threshold for effective natural pest control of 35% could be reached in the pesticide‐free areas of OSR fields adjacent to calcareous grasslands and flower fields maintained continuously for at least 6 years. In pesticide‐sprayed areas, pollen beetle parasitism and superparasitism declined with increasing distance to the adjacent field. Furthermore, flower fields larger than 1.5 ha were able to improve pollen beetle parasitism more than smaller fields. Synthesis and applications . To promote natural pest control in oilseed rape (OSR), large flower fields should be maintained for several years, to create stable habitats for natural enemies. The continuous maintenance of flower fields should be preferred, as ploughing and resowing after 5–6 years decreased the positive effects of the flower fields on natural pest control in adjacent OSR fields. However, pesticide use can abrogate positive effects of flower fields on pollen beetle parasitism. This study highlights that sown flower fields have the potential to increase natural pest control in OSR, but this potential is depending on its age, continuity and size and can be hindered by pesticide use. Abstract : To promote natural pest control in oilseed rape (OSR), large flower fields should be maintained for several years, to create stable habitats for natural enemies. The continuous maintenance of flower fields should be preferred, as ploughing and resowing after 5–6 years decreased the positive effects of the flower fields on natural pest control in adjacent OSR fields. However, pesticide use can abrogate positive effects of flower fields on pollen beetle parasitism. This study highlights that sown flower fields have the potential to increase natural pest control in OSR, but this potential is depending on its age, continuity and size and can be hindered by pesticide use.